Comparative genomics of Salmonella enterica serovars Paratyphi A, Typhi and Typhimurium reveals distinct profiles of their pangenome, mobile genetic elements, antimicrobial resistance and defense systems repertoire - Charles Coluzzi; Bar Piscon; Sandra Dérozier; Hélène Chiapello; Ohad Gal-Mor (Virulence)
Salmonella enterica (S. enterica) is a highly ubiquitous and diverse animal and human pathogen. Distinct S. enterica serovars may present varying host-specificity and cause different diseases. While the human-restricted serovars S. Typhi (STY) and S. Paratyphi A (SPA) cause in humans a systemic life-threatening enteric fever, the host-generalist serovar, S. Typhimurium (STM) causes in immunocompetent individuals a self-limited gastroenteritis. Here, we have performed whole-genome sequencing and hybrid assembly of new SPA and STY typhoidal strains and took a comparative genomics approach to examine their phylogeny, pangenome structure and accessory genome content in comparison to the reference non-typhoidal serovar, STM. Our results identified previously uncharacterized lineages of SPA and refined the presence and distribution of core pseudogenes in typhoidal serovars. Pangenome analysis showed that while these serovars have a relatively similar core-genome size, the accessory genome of STM is more than four times larger than those of typhoidal Salmonellae and that STY and SPA display a more closed pangenome than STM. Unexpectedly, we demonstrate that STY and SPA present distinct differences in their pangenome composition, with a noticeable lower number of prophages, conjugative elements and antimicrobial genes per genome in SPA vs. STY. These results suggest that although SPA and STY are closely related at the DNA level, share a similar lifestyle and cause a symptomatic-indistinguishable disease, their genomic evolution and accessory genomes are markedly different. Moreover, these results may provide genomic explanation to phenotypic and epidemiological differences in antimicrobial resistance profiles associated with these serovars globally.